Perspective and current state of international standards influence on prevention and treatment of diseases through the prism of developing high-quality and safe medicines - O. H. Aleksieiev (Zaporožskij Medicinskij Žurnal)
The aim of the work was to examine international legislation covering the legal responsibility in the pharmaceutical field; to analyze activities of international organizations in the area of combating counterfeit drug distribution.